Does Disclosure of Carbon Emission Able to Attract Investors? - Putikadea, Insyirah; Siregar, Cantika Sari (AKRUAL: Jurnal Akuntansi, 2023)
Introduction/Main Objectives: This study aims to examine the investor reaction to carbon emission disclosure as well as the impact of carbon emission disclosure on investor reaction through firm value. Background Problems: Carbon Emissions in Indonesia are one of the largest global carbon emitters, these issues encourage the firm to disclose their environmental concern which will affect the reputation and stakeholder’s reaction. Novelty: Some studies state about the effect of carbon emission disclosure on firm value and lack of studies result investigate the relation with reaction of investor. This study concern on the reaction of investor as impact of carbon emission disclosure, either directly or indirectly through firm value. Research Method: This study uses path analysis by SPSS. A total of 144 samples were collected from the basic materials sector, which is listed on the Indonesian Stock Exchange (IDX) over two representative periods. Finding/Results: The basic material sector is the primary sector of the firm’s value chain and is considered a stable sector that attracts the investor market. Nevertheless, this sector contributes to industrial emissions, such as carbon emission, which has become an essential issue in climate change that has become a stakeholder and customer concern. Conclusion: The study found that carbon emission disclosure impacts investor reaction directly; meanwhile, path analysis results showed that firm value could not mediate the effect of carbon emission disclosure towards investor reaction.